Aura in temporal lobe epilepsy: clinical and electroencephalographic correlation. Issue 12 (December 1983) - Gupta, A K; Jeavons, P M; Hughes, R C; Covanis, A
Abstract : Patients with temporal lobe epilepsy were evaluated for their aura and the site of EEG abnormality. Autonomic and psychic auras were more frequently associated with right-sided temporal lobe lesions in 290 patients.